Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpcc.5b10744
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Semiconducting PEDOT–TiO2/ZnO Hybrid Composites for Nanodevice Applications

Abstract: In this paper, we have developed a simple strategy for the preparation of hybrid nanocomposites of poly­(3,4-ethylenedioxythiophene)–TiO2/ZnO (PZT) and demonstrated its application in a thermoelectric device. Hierarchical hetero-nanostructured TiO2/ZnO (ZTO) was prepared by a facile sol–gel process in the presence of a biocapping agent. PZT was prepared by in situ polymerization of EDOT in the presence of ZTO. It was characterized by UV–visible, FT-IR, XRD, Raman, SEM, TEM, and AFM analyses. Results revealed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 66 publications
(107 reference statements)
1
14
0
Order By: Relevance
“…It is noteworthy that in case of CA3, the effective band gap is found to be the lowest (1.71 eV) which implies that Ag 2 O and CdS have large band bending and may have high carrier concentrations at room temperature. This turns out to be a very promising and an extremely beneficial approach for efficient visible light photocatalysis that will be discussed in the following section . It is also interesting to note that the structure and particle size of semiconductors play a major role in determining their photocatalytic activity …”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that in case of CA3, the effective band gap is found to be the lowest (1.71 eV) which implies that Ag 2 O and CdS have large band bending and may have high carrier concentrations at room temperature. This turns out to be a very promising and an extremely beneficial approach for efficient visible light photocatalysis that will be discussed in the following section . It is also interesting to note that the structure and particle size of semiconductors play a major role in determining their photocatalytic activity …”
Section: Resultsmentioning
confidence: 99%
“…Thanks to these properties, PEDOT has been reported to demonstrate high electrocatalytic activities for the oxygen reduction reaction [301], as well as an efficient catalyst in hydrogen generation and storage [302,303]. For this reason, PEDOT has been combined with many semiconducting metal oxides, such as TiO 2 [304], ZnO [305], or a combination of both metal oxides [306], determining an increase in the photocatalytic activity.…”
Section: Conductive Polymers-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…However, only a few polythiophene (PTh)-based composite photocatalysts have been actually reported and principally used for the photodegradation of organic pollutants and the CO 2 photoreduction [307]. [306] Definitely, the incorporation of conductive polymers has been demonstrated to significantly improve the visible-light-driven photocatalytic activity of hybrid nanostructured materials, by enhancing the separation of photogenerated charge carriers and extending the light absorption range. Based on these significant advantages, many nanostructured hybrids composed by semiconductor oxides conjugated with conductive polymers in different heterostructures have been designed, showing a promising photocatalytic activity, principally for water purification.…”
Section: Conductive Polymers-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…Namely, the carrier hopping barrier decreases in the PVP-coated GeO 2 NPs system, which increases the electrical conductivity. 26 This suggested that the PVP-coated amorphous GeO 2 NPs with low conductivity entered between the PEDOT molecules promoted one-dimensional electron conduction. Another possible reason is that the assembly of PEDOT-PSS changed from coiled to linear or extended conformation by PVP-coated GeO 2 NP incorporation.…”
Section: ¹1/2mentioning
confidence: 99%